Serum amyloid A1 (SAA1) protein in human colostrum - George H. Sack Jr; Natasha Zachara; Nadine Rosenblum; C. Conover Talbot Jr; Simion Kreimer; Robert Cole; Thomas L. McDonald (FEBS Open Bio)
Proteins of the serum amyloid A (SAA) family have been remarkably conserved in evolution. Their biologic function(s) are not fully defined but they are likely to be a part of primordial host defense. We have detected a ∼ 12‐kDa protein reacting with antibodies against serum amyloid A (SAA) in human colostrum by western blotting. Mass spectrometry identified the reactive species as SAA1, previously identified as a prominent member of the acute‐phase response in serum. Our finding SAA1 in human colostrum contrasts with bovine, caprine and ovine colostrum where a species corresponding to putative SAA3 is uniformly present. SAA1 protein in human colostrum presumably contributes to neonatal protection.